The most influential sources of psychological stress on physical education and sports teachers - rachid aman allah; hbara mohamed (sports creativity, 2025)
One of the most significant characteristics of human life at the end of the 20th and the beginning of the 21st centuries is the accelerated pace of life and the communications revolution that has transformed the world into a global village. This is further compounded by the integration of technology into all aspects of daily life, including education, industry, trade, agriculture, medicine, and transportation. Additionally, the global economy has shifted towards a free market system. All these major changes in lifestyle present a challenge to human capabilities, requiring individuals to understand and cope with them. Consequently, these changes create psychological pressures for people in this era, and they must adapt to them. While some pressures may be manageable, others may prove more challenging. Work-related stress is a significant aspect of life's pressures; it is a psychological phenomenon, like anxiety and aggression, and cannot be denied. It must be addressed by specialists to help workers adapt to their jobs, ultimately leading to increased productivity and quality, and consequently, societal development and progress. According to the International Labour Organization, teaching is considered one of the most stressful professions due to the numerous pressures inherent in the educational environment. While addressing the phenomenon of work-related stress in general is important, addressing the stress of the teaching profession is far more critical. This stems from the serious consequences of prolonged stress, which can ultimately lead to psychological burnout, resulting in individual exhaustion, decreased efficiency, and increased negative impacts on their lives (see Laila Othman Ibrahim Othman, 1987, p. 12). The frequent protests and open-ended strikes undertaken by secondary school teachers in recent years, which have paralyzed educational institutions for extended and intermittent periods, demonstrate teachers' rejection of their current professional reality. They are striving for better working conditions and a more secure and stable job environment. Therefore, to diagnose the phenomenon of psychological stress among physical education and sports teachers, we decided to conduct a field-based psychological study, grounded in clear scientific and methodological principles, to investigate the reality of psychological stress within this group and identify its sources and causes. This study comprises nine chapters.